Post‐disturbance haulout behaviour of harbour seals. (6th September 2019) - Paterson, William D.; Russell, Debbie J.F.; Wu, Gi‐Mick; McConnell, Bernie; Currie, John I.; McCafferty, Dominic J.; Thompson, Dave
Abstract: The impact of anthropogenic activity associated with marine renewable developments on harbour seals ( Phoca vitulina ) was investigated using controlled disturbance trials. Hauled‐out seals were approached by boat until all seals had entered the water, and this was repeated approximately every 3 days (weather permitting). The time taken for seal counts to return to pre‐disturbance levels was determined by monitoring haulout sites using time‐lapse photography. Mean post‐disturbance counts of hauled‐out seals returned to 52% (95% confidence interval [CI] 35–69%) of pre‐disturbance counts within 30 min. However, mean counts only returned to 94% (95% CI 55–132%) of pre‐disturbance counts after 4 hr. Eight seals were tagged with Global Positioning System phone tags to provide information on haulout location and at‐sea movements, allowing investigation of how disturbance may influence haulout site choice and seal distribution. Telemetry‐tagged seals displayed a high degree of haulout site fidelity. Disturbance trials did not have a significant effect on the probability of seals moving to a different haulout site. When seals hauled out again within the same low‐tide period after disturbance trials, the proportion of time spent hauled out was high, indicating that when seals are motivated to haul out they will do so despite past disturbance. Motivation to haul out more on disturbance trial days was not linked to a cyclic pattern of hauling out more over consecutive low‐tide periods. As there was no large‐scale redistribution after disturbance, we suggest that monitoring effort to determine the effects of short‐term increases in levels of disturbance caused by boat activity can be spatially localized. However, where disturbance is likely to be longer term or impact on important haulout sites for breeding and/or moulting, monitoring may be required over a larger geographical area.